Anticancer activities of Styrylpyrone from the Leaves and Twigs of Goniothalamus maewongensis via cell cycle arrest - Pradit Pradupsri (2018)
Problem statement: Goniothalamus maewongensis is one of three new species which are found in Thailand recently. The genus goniothalamus is not only well known for the rich of styrylpyrones but also famous for the potential of biological activities, especially the cytotoxic activity against a number of human cancer cell lines. The phytochemical and biological investigations of this plant are interesting to bioassay-guided fractionation, particularly cell cycle arrest. Approach: The investigation was carried out to extract, isolate, purify and elucidate structure of the active compound from the leaves and twigs of Goniothalamus maewongensis. Both of the solvent extracts and isolated compound were evaluated with kinds of mammalian cancer cell lines, i.e., A549, GLC4, GLC4/Adr, K562 and K562/Adr for antiproliferation assay and cell cycle analysis. Results: Styrylpyrone from the leaves and twigs of Goniothalamus maewongensis was isolated from the active hexane extract. The spectroscopic techniques were provided for success in structure elucidation. In addition, a styrylpyrone compound was the most powerful to biological activities, which this molecular is significantly more toxic to small cell lung cancer than non small cell lung cancer cell (p<0.05). On the other hand, the goniodiol was not recognized by both multidrug resistance protein (ABCC1 and ABCB1). The study of cell cycle arrest explained antiproliferation effect by goniodiol at G2/M arrest in both lung cancer type (A549 and GLC4) and erythroleukemia cell (K562), while cell cycle arrest by goniodiol on both resistant cell lines are positioned on G0/G1 or S-phase. Conclusion: Goniodiol exhibits anti-proliferative on cancer cell line and un-recognized by multidrug resistant protein (ABCB1 and ABCC1). © 2009 Science Publications.